2021
DOI: 10.1089/thy.2020.0299
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Dietary Habits on Oxidative Stress Markers in Hashimoto's Thyroiditis

Abstract: Background: There is a growing awareness that nutritional habits may influence risk of several inflammatory and immune-mediated disorders, including autoimmune diseases, through various mechanisms. The aim of the present study was to investigate dietary habits and their relationship with redox homeostasis in the setting of thyroid autoimmunity. Materials and Methods: Two hundred subjects (173 females and 27 males; median age, 37 years) were enrolled. None were under any pharmacological treatment. Exclusion cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 44 publications
5
65
0
Order By: Relevance
“…It has to be underlined that all our patients were euthyroid and, therefore, no alteration of oxidative stress parameters could be attributed to overt or subclinical hypothyroidism, since we decided to recruit only patients with euthyroid HT at diagnosis. The links between AGEs, sRAGE, and AOPPs and HT have been already investigated in adults [22, 31, 32]. In particular, significantly higher serum levels of AGEs and lower serum levels of sRAGE have been documented among HT patients than controls [22, 31, 32].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has to be underlined that all our patients were euthyroid and, therefore, no alteration of oxidative stress parameters could be attributed to overt or subclinical hypothyroidism, since we decided to recruit only patients with euthyroid HT at diagnosis. The links between AGEs, sRAGE, and AOPPs and HT have been already investigated in adults [22, 31, 32]. In particular, significantly higher serum levels of AGEs and lower serum levels of sRAGE have been documented among HT patients than controls [22, 31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…The links between AGEs, sRAGE, and AOPPs and HT have been already investigated in adults [22, 31, 32]. In particular, significantly higher serum levels of AGEs and lower serum levels of sRAGE have been documented among HT patients than controls [22, 31, 32]. In our study, we demonstrated that euthyroid children with HT had lower serum levels of sRAGE, notwithstanding that significant differences in AGEs, AOPPs, and AGEs/sRAGE have not been documented.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Advanced glycation end products (AGE) are believed to be associated with the onset and progression of metabolic disorders, notably diabetes and obesity, due to their formation both through lipid peroxidation and glycoxidation reactions; that is, in response to an increased intake of simple carbohydrates [15,63]. Elevated levels are observed in ROS-damaged tissues, as the final product of peroxidation, making them markers of oxidative stress in the body [64]. Among DNA bases, guanine is the most easily oxidised, due to its relatively low redox potential.…”
Section: Biomarkers Of Oxidative Stress In Thyroid Diseasesmentioning
confidence: 99%